GraphoLearn India: The Effectiveness of a Computer-Assisted Reading Intervention in Supporting Struggling Readers of English - Patel, Priyanka; Torppa, Minna; Aro, Mikko; Richardson, Ulla; Lyytinen, Heikki (Frontiers in Psychology, 2018)
India, a country with a population of more than 1.3 billion individuals, houses the world's second largest educational system. Despite this, hundreds of millions of individuals in India are still illiterate. As English medium education sweeps the country, many are forced to learn in a language which is foreign to them. Those living in poverty further struggle to learn English as it tends to be a language which they have no prior exposure to and no support at home for. Low-quality schools and poor instructional methods further exacerbate the problem. Without access to quality education, these individuals continue to struggle and are ultimately never given the chance to break the cycle of poverty. The aim of this study was to determine whether GraphoLearn, a computer-assisted reading tool, could be used to support the English reading skills of struggling readers in India. Participants were 7-year-old, grade 3 students (N=30), who were attending an English-medium public school in Ahmedabad, India. English was not a native language for any of the students and all were reading at a level below that of Grade 1 despite having attended school for 2 years. Half of the students played GraphoLearn (n=16) while the other half played a control math game (n=14) for 20-30 minutes a day, over a period of 8 weeks. GraphoLearn led to significant improvements in children's letter-sound knowledge, a critical factor in early reading development. Overall, the study opens doors for GraphoLearn as a potential intervention to support struggling readers of English in India, including those who are learning a non-native language and coming from at-risk backgrounds.